YES Problem: a(a(x)) -> a(b(a(x))) b(a(b(x))) -> a(c(a(x))) Proof: AT confluence processor Complete TRS T' of input TRS: a(a(x)) -> a(b(a(x))) b(a(b(x))) -> a(c(a(x))) T' = (P union S) with TRS P: TRS S:a(a(x)) -> a(b(a(x))) b(a(b(x))) -> a(c(a(x))) S is linear and P is reversible. CP(S,S) = a(a(b(a(x23)))) = a(b(a(a(x23)))), b(a(a(c(a(x24))))) = a(c(a(a(b(x24))))) CP(S,P union P^-1) = CP(P union P^-1,S) = We have to check termination of S: Matrix Interpretation Processor: dim=3 interpretation: [1 0 1] [0] [b](x0) = [0 0 0]x0 + [1] [0 0 0] [0], [1 0 1] [0] [a](x0) = [0 0 0]x0 + [1] [0 1 0] [0], [1 0 0] [c](x0) = [0 0 0]x0 [0 0 0] orientation: [1 1 1] [0] [1 1 1] [0] a(a(x)) = [0 0 0]x + [1] >= [0 0 0]x + [1] = a(b(a(x))) [0 0 0] [1] [0 0 0] [1] [1 0 1] [1] [1 0 1] [0] b(a(b(x))) = [0 0 0]x + [1] >= [0 0 0]x + [1] = a(c(a(x))) [0 0 0] [0] [0 0 0] [0] problem: a(a(x)) -> a(b(a(x))) Matrix Interpretation Processor: dim=2 interpretation: [2 0] [2] [b](x0) = [0 0]x0 + [0], [1 1] [0] [a](x0) = [1 1]x0 + [3] orientation: [2 2] [3] [2 2] [2] a(a(x)) = [2 2]x + [6] >= [2 2]x + [5] = a(b(a(x))) problem: Qed